Development of Polymer Composite Electrode to Analyze Metformin Hydrochloride Drug in Pharmaceutical Formulation with Higher Current Response - Tiwari, D.C.; Jain, Rajeev; Sharma, S. (Asian Journal of Chemistry, 2011)
A composite polymer of polyaniline (PANI) and polypyrrole (PPy) was coated on a tin oxide slide, offers improvement in voltammetric detection system compared to conventional platinum electrode. Polyaniline/polypyrrole composite electrode was developed by electrochemical deposition technique and standardize as a working electrode in cyclic voltammetric technique for the detection of metformin hydrochloride (MET) drug. Metformin hydrochloride is a drug used for diabetics patients gave one well defined reduction peak (c1 at 220 mV) and one oxidation peak (a1 at 1266 mV) at composite polymer electrode. The results are compared with that of a platinum electrode (c1 at 740 mV and a1 at 1308 mV, respectively). It was observed that the peak current increases significantly at pH = 3 on the composite polymer electrode and both reduction and oxidation peak potentials shift to lower potential than that of potential observed at platinum electrode. It indicates catalytic behaviour of composite polymer electrode for the analysis of metformin hydrochloride. A cyclic voltammetric method for determination of metformin hydrochloride at composite polymer electrode is proposed in this paper. The best results for the oxidation of metformin hydrochloride at pH = 3 with composite polymer electrode were obtained at a potential of 1266 mV in presence of Ag/AgCl reference electrode.